Die motoriese ontwikkeling van en prestasiestandaarde vir dogters van 11 tot 16 jaar / Johannes Petrus le Roux - Le Roux, Johannes Petrus (Potchefstroom University for Christian Higher Education, 2013)
Research in connection with the female is nothing new in Physical Education. It is a generally accepted fact that the female need not play second fiddle to the male. Misconceptions with regard to the place of the female in society as well as her place in sport have long since disappeared. It is thus? logical that the education of the female in all its ramifications should enjoy the same degree of attention as that of the male. In older European countries and especially in the U.S.A. much research has been done in connection with the Physical Education of the female. In South Africa research in this connection has not lagged behind. Various problems have already been satisfactorily solved, some have had less satisfactory results while others have not been touched. The necessity for an investigation into the performance of white South Africans has partly been satisfied by the researches of Van der Merwe and Van Zyl (Chapter 3). Research projects in this field have already been done overseas. It is, however, known that the tests and their results based on a specific group of people are only applicable to that group, except if the opposite can be scientifically proved. Another important investigation into Physical Education of white South African girls has been done by De Jager. (Chapter 3). In this research work he studied the influence of chronological age upon the motor-performance of white school girls.